STUDI DESKRIPTIF PERAN PENDIDIKAN KRISTEN DALAM MENYIKAPI K-POP - Vena Melinda Tiladuru; Aji Suseno; Yonatan Alex Arifianto (STT Bethel The Way, 2021)
Abstract: Korean Wave (K-pop) is a popular culture that is so favored by teenagers, it has made local culture shift. The transfer of Korean Pop Culture spreads widely through social networks as if it could not be prevented. The entertainment industry, music, films, magazines and other aspects always present everything that is synonymous with Korean culture. Opium from Korean Pop Culture has a devastating impact on adolescents as a result (1) fanaticism of Indonesian teenagers makes it more interested in exploring Korean culture, (2) Not passionate about learning, (3) wasteful lifestyle, (4) The emergence of fanfic no child which leads to pornography and porno-action. This research method uses a qualitative description by describing the K-pop phenomenon that occurs in adolescents and how to deal with the impacts experienced by adolescents, especially Christian teenagers in Indonesia. The results of this study indicate that the handling of Christian adolescents who experience K-pop addiction can be started from the environment where they grew up, among others, the family environment, educational environment, church environment. Both families, schools, churches as well as other youth formation groups have a role to play in instilling Christian values ​​that lead them to experience spiritual growth. When the youth environment continues to introduce who Christ is for their lives, the example needed by youth has been answered through the example in Jesus Christ.